Prevalence of the Catatonic Syndrome in an Acute Inpatient Sample - Stuivenga, Mirella; Morrens, Manuel (Frontiers in Psychiatry, 2014)
OBJECTIVE: In this exploratory open label study we investigated the prevalence of catatonia in an acute psychiatric inpatient population. In addition, differences in symptom presentation of catatonia depending on the underlying psychiatric illness were investigated. METHODS: 130 patients were assessed with the Bush-Francis Catatonia Rating Scale (BFCRS), the Positive and Negative Syndrome Scale (PANSS), the Young Mania Rating Scale (YMRS) and the Simpson-Angus Scale (SAS). A factor analysis was conducted in order to generate 6 catatonic symptom clusters. Composite scores based on this principal component analysis were calculated. RESULTS: When focusing on the first 14 items of the BFCRS, 101 patients (77.7%) had at least 1 symptom scoring 1 or higher, whereas 66 patients (50.8%) had at least 2 symptoms. Interestingly, when focusing on the DSM-5 criteria of catatonia, 22 patients (16.9%) could be considered for this diagnosis. Furthermore, different symptom profiles were found, depending on the underlying psychopathology. Psychotic symptomatology correlated strongly with excitement symptomatology (r=.528,p<.001) and to a lesser degree with the stereotypy/mannerisms symptom cluster (r=.289; p=.001) and the echo/perseveration symptom cluster (r=.185;p=.035). Similarly, manic symptomatology correlated strongly with the excitement symptom cluster (r=.596;p<.001) and to a lesser extent with the stereotypy/mannerisms symptom cluster (r=.277;p=.001). CONCLUSION: There was a high prevalence of catatonic symptomatology. Depending on the criteria being used, we noticed an important difference in exact prevalence, which makes it clear that we need clear-cut criteria. Another important finding is the fact that the catatonic presentation may vary depending on the underlying pathology, although an unambiguous delineation between these catatonic presentations cannot be made. Future research is needed to determine diagnostical criteria of catatonia which are clinically relevant.